Given data:
The first set of equations are x+y=4, and x=6.
The second set of equations are 3x-y=12 and y=-6.
The point of intersection of first set of te equations is,
6+y=4
y=-2
The first point is (6, -2).
The point of intersection of second set of te equations is,
3x-(-6)=12
3x+6=12
3x=6
x=2
The second point is (2, -6).
The equation of the line passing through (6, -2) and (2, -6) is,
![\begin{gathered} y-(-2)=(-6-(-2))/(2-6)(x-6) \\ y+2=(-6+2)/(-4)(x-6) \\ y+2=x-6 \\ y=x-8 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/pkpkfo14xdal9zhym7ysq5hm82i0w0tnu7.png)
Thus, the required equation of the line is y=x-8.